Perangkingan Potensi Guru dalam Penentuan Calon Kepala Sekolah Menggunakan Metode TOPSIS - Bendra Wardana; S Sumijan (Rektorat Universitas Putra Indonesia YPTK Padang, 2021)
Efforts to increase the value of the quality of education for students as the next generation of the nation require teachers who have competence in providing education to students. The competence of a teacher can be assessed when a teacher has carried out his duties in accordance with the standard provisions he has. The ranking of potential teachers is used to motivate teachers to be active in carrying out each activity and is expected to have a positive effect on their work to face challenges in this era of globalization. The data that is processed for the ranking of teacher potential is the assessment data of elementary school teachers sourced from the korwildik of the Batang kapas sub-district. This ranking is based on several criteria and weights are determined. Furthermore, this ranking is processed using a system created by the researcher. This ranking uses a method called TOPSIS to assist researchers in ranking. The TOPSIS method is a multi-criteria decision support method with the principle that the chosen alternative must have the closest distance from the positive and negative ideal solutions. The results of ranking with the TOPSIS method are able to support the ranking decisions of potential teachers using predetermined criteria. So that the highest value is found in the 5th alternative with a value of 0.7321 and the lowest value is found in the 1st alternative with a value of 0.2218. The ranking of potential teachers has proven to be able to help the South Coast District Education and Culture Office, especially the korwildik of the Batang kapas sub-district in determining prospective school principals.